An estimation of CO2 emission via agricultural crop residue open field burning in China from 1996 to 2013. (20th January 2016) - Sun, Jianfeng; Peng, Haiyun; Chen, Jianmin; Wang, Xinming; Wei, Min; Li, Weijun; Yang, Lingxiao; Zhang, Qingzhu; Wang, Wenxing; Mellouki, Abdelwahid
Abstract: The field burning of agriculture straw residue is a common method to dispose waste after harvesting seasons in China. The burning of agricultural crop residue in open field which has been given little attention up till now represents an important source of CO2 for global warming concern. According to the CO2 emission factors of rice, wheat, and corn straws based on laboratory measurements, the amount of CO2 emission via agricultural crop residue open burning in China between 1996 and 2013 has been calculated. The diverse accounting methods and geographic information system (GIS) are used to map the CO2 emission of thirty-one provinces. Identifying the spatial distribution, 5-year average variation, and contributions of CO2 emission by three major agricultural residue open burning, it is found: (i) About 2707.34 Tg of CO2 is emitted by agriculture residue open burning, occupies 45.09% of the total residential coal consumption from 1996 to 2013 (ii) The total emission from rice, wheat and corn straw burning are concentrated in south and northeast of China, North China and northeast of China, respectively (iii) Shandong Province contributes the largest portion of CO2 emission, Henan, Jiangsu, Hebei and Hei Longjiang rank the second, third, forth, and fifth, respectively. From different level of CO2 emission by agricultural crop residue open burning, we can find mitigation potential of greenhouse gas emission and give three suggestions: (i) generalizing straw returning field application (ii) improving the efficiency of straw utilization (iii) commercializing biomass energy. However, the mitigation potential, and varied policies and regulations need to be developed which are related to the local economic and environmental conditions in different China rural places. Highlights: 2707.34 Tg of CO2 was emitted by crop residue open burning, occupies 45.09% of the total residential coal consumption. The top five provinces of CO2 emission rank Shandong>Henan>Hebei>Jiangsu>Hei Longjiang. Burning of rice, wheat and corn straw concentrated in eastern and southern of China, North China and northeastern of China.